Paramagnetic Gd3+ labeled red blood cells for magnetic resonance angiography. (August 2016) - Aryal, Santosh; Stigliano, Cinzia; Key, Jaehong; Ramirez, Maricela; Anderson, Jeff; Karmonik, Christof; Fung, Steve; Decuzzi, Paolo
Abstract: Despite significant advances in contrast enhanced-magnetic resonance angiography, the lack of truly blood-pool agents with long circulating property is limiting the clinical impact of this imaging technique. The terminal half-life for blood elimination of most small molecular weight gadolinium (Gd) based extracellular fluid agents is about 1.5 h when administered intravenously to subjects with normal renal function. The small size of these extracellular fluid agents does not prevent them from extravasating, especially from damaged vessels which are generally hyperpermeable. Therefore, the development of novel, clinically relevant blood pool contrast agents is critically needed to improve outcomes in the prevention, detection, and treatment of vascular diseases. We have demonstrated the fusion strategies in which the Gd-liposome without any stealth property radically fuses with red blood cells (RBCs) forming MR glowing Gd-RBC with the order of magnitude enhancements in circulation half-life (t1/2 = 50 h) and r1 relaxivity (r1 = 19.0 mM −1 s −1 ) of Gd. The in vivo contrast enhancement of Gd-RBC was studied by using 3T clinical MR scanner for extended period of time, which clearly visualized the abdominal aorta. In summary, the vascular delivery of blood pool agents may benefit from carriage by RBCs because it naturally stays within the vascular lumen.